An Inch or Two of Time : Time and Space in Jewish Modernisms - Finkin, Jordan D., 1976- (Book collections on Project MUSE., 2015)
"Explores the metaphorical power of time and space in Jewish modernist poetry in Hebrew and Yiddish as a response to the experience of exile and landlessness, and as a means of furthering modernism's exploration of the self and its relation to community, nation, and the world"--Provided by publisher.